The effect of cultural background on comprehension of English texts by second language learners of English - Emsley, Maletsema Ruth (University of Limpopo, 2011)
This study investigated the effect of cultural background on comprehension of English texts by second language learners. The study specifically aimed at determining whether cultural background had any effect on comprehension of English texts by second language learners and whether the second language learners’ cultural background could help them comprehend unfamiliar texts. The background of the study in this mini dissertation was followed by the discussion on the literature available on this topic. This study followed a case study design which utilized 89 respondents from the Further Education and Training band of a rural secondary school in the north of Limpopo province. Data was obtained through the completion of questionnaires and answering of questions from a comprehension test based on English culture. The findings showed that there was no total comprehension of the text by learners who use English as a second language. Learners of English as a second language need to possess specific cultural schemata to comprehend texts that are unfamiliar to them. This study was informed by the schema theory. There is a significant effect of cultural background on the comprehension of English text by second language learners. KEY WORDS: Schema theory. Culture Comprehension. Cultural background
Thesis (M.Ed. (Language Education)) --University of Limpopo, 2011.
Keywords: Schema theory; Culture; Cultural background; 372.623049; English language -- Study and teaching -- Foreign speakers; English language -- Textbooks for foreign speakers